UMP riders club portal (URCP) - Mohamad Noriman, Tumiran (2014)
Nowadays, many portal systems are developed where it is to facilitate users to interact online where, it displays the latest information according to a particular category. This is because, the online system has many advantages compared using a manual system. This Portal developed caused by problems faced by the management UMP Riders Club in the student registration process where, they are having problems in data storage because the registration is done manually and all student registration information stored in files. By this method, it is exposed to loss, theft and damage data. Generally, registration method manually unsatisfactory some people and take longer time to process data. Accordingly to this problem, UMP Riders Club developed to improve the quality of management of UMP Riders Club. It also helps to facilitate the students to make registration and will also satisfy both sides.